2013
DOI: 10.2355/tetsutohagane.99.635
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Performance of High Temperature Steel Plate in Intensive Cooling with High Water Flow Rate

Abstract: 緒言Upperlimitofcoolingperformancewasnotfoundintherangeofexperimentalconditions.At highersurfacetemperature,whereismorethan1000ºC,coolingperformanceatuppersurfaceismuchlargerthanatlowersurface,whereas difference of cooling performance between upper surface and lower surface is small at lower temperature. Effect of transfer speed was not seenincoolingtimeof0.2-0.3s.Basedonexperimentaldataandthermalanalysis,equivalentheattransfercoefficientwascalculatedtobe10-29MW/m 2 K,whichisextremelyhigherthaninliteraturedata.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…5) Water cooling tests were conducted at relatively high plate surface temperatures in the range of 850-1 100°C with relatively shorter cooling times of 0.2-0.3 s and intensive, high flow rate water cooling, and the effects of the water flow rate, plate surface temperature and transfer speed on cooling intensity were clarified. Those tests were performed by using a header in which hole nozzles with the inner diameter of φ3 mm were arranged in an area of 300 mm × 300 mm.…”
Section: Evaluation Of Cooling Performance In Intensive Cooling With mentioning
confidence: 99%
“…5) Water cooling tests were conducted at relatively high plate surface temperatures in the range of 850-1 100°C with relatively shorter cooling times of 0.2-0.3 s and intensive, high flow rate water cooling, and the effects of the water flow rate, plate surface temperature and transfer speed on cooling intensity were clarified. Those tests were performed by using a header in which hole nozzles with the inner diameter of φ3 mm were arranged in an area of 300 mm × 300 mm.…”
Section: Evaluation Of Cooling Performance In Intensive Cooling With mentioning
confidence: 99%
“…Wang et al 25) experimentally studied the transient cooling process of a static stainless steel plate by downward and upward circular jet impingement, and reported differences between the two temperature histories of the solid. Nakata et al 26,27) recently studied the intensive cooling of hot moving steel at a high water flow rate. They showed that the orientation of the solid surface affects the heat transfer characteristics.…”
Section: Boiling Heat Transfer Characteristics Of Vertical Water Jet mentioning
confidence: 99%
“…Nakata et al 26,27) recently studied the cooling of hot moving steel using intensive cooling at high water flow rate. They reported that the temperature drop in the steel plate for a downward-impinging jet was greater than that for the upward jet because of the presence of the residual liquid.…”
Section: Comparison In Terms Of Heat Transfer Character-mentioning
confidence: 99%